Computational modeling and forensic analysis for terrorist airplane bombing: A case study. (15th April 2019) - Yeh, Jean; Chen, Goong; Gu, Cong; Thurman, James "Tom"; Sergeev, Alexey; Wei, Chunqiu; Zhu, Jing; Hajaiej, Hichem; Shang, Ying-Feng; Zhu, Feng; Tahir Mustafa, M.
Highlights: Contains practice, modeling and computation. Dynamics is illuminated by supercomputer results of videos. Event reconstruction and forensic assessments are made for Daallo Airlines Flight 159 bombing case. Abstract: The bombing of airliners has been a tactic used by terrorists during the past 40 years. Its prevention is a major priority by homeland security officials on a worldwide basis. In efforts to aid in the investigation of such bombings, this paper provides the results of the development of mathematical modeling and computer simulation for the study of aircraft bombings and associated forensics. As an assist in the forensic study, a number of photographs are provided to depict the normally observed physical characteristics of explosives damage upon aircraft and related materials. Our study illuminates and evaluates how these characteristics can be captured by computational mechanics. Finally, we use the laptop bombing of Daallo Airlines Flight 159 as a case study to demonstrate that event reconstruction can be accomplished for the purpose of forensic investigations. Most of our supercomputer results are visualized by video animations in order to show the dynamic effects and phenomena of explosives and the associated event reconstruction.